Aktuelle Trends bei der Behandlung rhegmatogener Netzhautablösungen und perioperative Lagerungsstrategien in Deutschland: Ergebnisse einer retina.net-Umfrage - Strzałkowski, Piotr; Strzalkowska, Alicja; Stahl, Andreas; Schuster, Alexander K.; Kaya, Sema; Roth, Mathias; Krohne, Tim U.; Finger, Robert P.; Schaub, Friederike; Dithmar, Stefan; Framme, Carsten; Wolf, Armin; et al. (Die Ophthalmologie, 2025)
Background Rhegmatogenous retinal detachment (RRD) is an ophthalmological emergency with an increasing incidence in Germany. Despite established methods, perioperative positioning is important to improve outcomes and avoid complications but may be challenging, particularly in immobile patients. An analysis of the current trends in surgical treatment and perioperative positioning practices for RRD in Germany compared to historical data from 2018 is essential. Material and methods An online survey with five hypothetical cases of acute RRD was distributed to vitreoretinal surgeons via the retina.net research network. A total of 27 questionnaires were analyzed focusing on participant demographic data, surgical techniques, anesthesia types, perioperative positioning and aftercare strategies. Results Of the respondents 50% were over 50 years old, 86% worked at university eye clinics and 89% had performed over 1000 vitreoretinal procedures. For RRD in the temporal upper quadrant, preoperative and postoperative temporal lateral positioning is recommended. Of the respondents 86% consider postoperative positioning crucial to prevent macular folds. Complete subretinal fluid drainage is favored by 82% and 23G trocars were used by 77%. For phakic eyes with uncomplicated RRD 86% chose buckling surgery, while 50% opted for silicone oil in complex inferior RRD cases. General anesthesia was preferred by 61%, always in an in-patient setting. Conclusion Preoperative and postoperative temporal lateral positioning followed by prone positioning is favored for temporal upper quadrant RRD, whereas no specific positioning is recommended for inferior RRD managed with silicone oil or buckling surgery. Postoperative positioning after pars plana vitrectomy (ppV) and gas endotamponade is considered by 86% to be decisive in preventing macular folds. The 23G trocar system remains the preferred choice despite smaller alternatives. In certain cases buckling is still of importance.
Online veröffentlicht: 24. März 2025
Gesehen am 26.05.2025